Synthesis of nanopowders by the glycine-nitrate method in the In-Dy-O system; Chimica Techno Acta; Vol. 10, iss. 3 - Malinovskaya T. D. Tatjyana Dmitrievna; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Aparnev A. I. Alexander; Zhek V. V. Valentina Vladimirovna (2023, 2023)
Title screen